Impact of Teachers Training on Interest and Academic Achievements of Students by Multiple Teaching Methods - Muhammad Hafeez (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
A research has been conducted to check the effects of teachers training and teaching methods on academic achievements and interests of students at secondary schools in computer course. The population is divided into four groups; - lecture teaching method (control group), discussion teaching method (experimental method), inquiry teaching method (experimental group) and demonstration teaching method (experimental group). Each group has a sample size of 20 students. A pre-test before training of teachers and post-test after training of teachers for academic achievement and interests of students taught by four teaching methods have been conducted. The results of pre and post-tests are then analysed statistical tools of descriptive statistics and ANOVA test. The results of the study indicated that students academic achievements and interests have been increased before and after the training of the teachers taught by lecture, discussion, inquiry and demonstration teaching methods. The demonstration teaching method was ranked 1st and lecture teaching method was ranked last.